2020
DOI: 10.1177/0894845320949706
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Racial Microaggressions and Bicultural Self-Efficacy on Work Volition in Racially Diverse Adults

Abstract: We investigated the relationship between racial microaggressions and work volition in a sample of racially diverse adults ( N = 171) in the United States for this online cross-sectional study. Correlation analyses revealed that higher levels of racial microaggressions across five of the six racial microaggression dimensions (i.e., criminality, environmental invalidations, foreigner, invisibility, and low-achieving/undesirable culture) related to lowered work volition. We explored how the relationship between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…Contrary to the previous PWT finding with employed women (predominantly White; England et al, 2020) or racially diverse adults in the United States (Marks et al, 2020), no relationship was reported between microaggressions and work volition among Asian American women. Furthermore, work volition did not mediate the effect of gendered racial microaggressions on decent work.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the previous PWT finding with employed women (predominantly White; England et al, 2020) or racially diverse adults in the United States (Marks et al, 2020), no relationship was reported between microaggressions and work volition among Asian American women. Furthermore, work volition did not mediate the effect of gendered racial microaggressions on decent work.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, work volition did not mediate the effect of gendered racial microaggressions on decent work. This may be because our study focused on gendered racial microaggressions in a broad context not specific to the workplace or potential factors may mediate or moderate the relationship between microaggressions and work volition (e.g., bicultural self-efficacy; Marks et al, 2020). Given that work volition represents an important attitudinal variable within the PWT, the current findings call for further exploration of possible factors associated with work volition that explains how marginalized experiences can link to limited access to decent work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing patterns of dyadic bicultural competence indicate differing levels of ability to cope with challenges associated with dominant and heritage cultures. Individual bicultural competence has been associated with increased ability to cope with culturally based challenges, including seeking employment (Marks et al, 2022) and managing academic demands (Diemer, 2007). As with individual bicultural competence, high dyadic bicultural competence couples will be more effective across a wider range of cultural contexts than if both partners identified with only one culture.…”
Section: Pathway Cmentioning
confidence: 99%
“…Career practitioners should be knowledgeable about multiple events of racial injustice and violence that can overload the physical, cognitive, and emotional fatigue of BIPOC clients (Fortuna et al., 2020; Misra et al., 2020 ). Career practitioners can be attentive and willing to broach the confluence of racial injustice with career development (Kantamneni, 2020 ), especially as opportunity foreclosure, job loss, and racism in the workplace have been symptoms of pervasive societal issues in the United States (see Cornileus, 2013 ; Marks et al., 2020 ; Tovar‐Murray et al., 2012 ). In this vein, career practitioners can discuss how experiences of racism and COVID‐19 cascade the effect of trauma (Liu & Modir, 2020 ) and alter perceptions of choice (SAMHSA, 2014 ).…”
Section: A Framework Of Ticmentioning
confidence: 99%